2016
DOI: 10.21930/rcta.vol18_num1_art:556
|View full text |Cite
|
Sign up to set email alerts
|

Pequeños productores de maíz en el Caribe colombiano: estudio de sus atributos y prácticas agrícolas

Abstract: <p><span>La agricultura familiar es la responsable de la mayor<span class="apple-converted-space"> </span>parte de la producción de los alimentos en América<span class="apple-converted-space"> </span>Latina. Sin embargo, es evidente que las innovaciones tecnológicas desarrolladas para mejorar la productividad del cultivo de maíz Zea mays L. (Poaceae) no son del todo utilizadas por los pequeños productores. Con el objetivo de evaluar los atributos sociales, económicos y ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…The results reveal, in general, a low (G I , G II, and G III ) to medium (G IV and G V ) technological level in eggplant production in the Colombian Caribbean region. In this regard, some studies have found that aspects, such as the technological level and the adoption of technologies, have a direct relationship with the schooling level of farmers (Damián and Ramírez, 2008;Aguilar et al, 2013;Ayala et al, 2013;Vargas et al, 2015;Garrido et al, 2017). This is consistent with the results obtained in this study, in which the groups with the highest level of education (G IV and G V ) showed the highest yields (G IV = 35 t ha -1 , G V = 32 t ha -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results reveal, in general, a low (G I , G II, and G III ) to medium (G IV and G V ) technological level in eggplant production in the Colombian Caribbean region. In this regard, some studies have found that aspects, such as the technological level and the adoption of technologies, have a direct relationship with the schooling level of farmers (Damián and Ramírez, 2008;Aguilar et al, 2013;Ayala et al, 2013;Vargas et al, 2015;Garrido et al, 2017). This is consistent with the results obtained in this study, in which the groups with the highest level of education (G IV and G V ) showed the highest yields (G IV = 35 t ha -1 , G V = 32 t ha -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although preliminary results of each isolated variable could be discussed in the light of studies carried out by various authors (Aguinsaca-Caraguay, 2014; Crespo et al, 1996;Forero-Camacho et al, 2013;Garrido-Rubiano et al, 2017;Villalba et al, 2016), we consider that their transcendence for this work would be relative, because these were carried out in an aggregate way and therefore, these show interactions with each other (e.g. between age and extra-farm income).…”
Section: -78mentioning
confidence: 96%
“…On one hand, structural variable studies can be useful to make an approximate prediction of how the farm will behave depending on diverse situations, as a proposal of technological change (Kaminsky, 1988). In specialized literature consulted regarding this topic and that was mostly selected for the study region, references were found on numerous structural variables; among these, the most repeated ones were prioritized with the sole intention of showing a general idea about the type of variables involved: size of the farm or its form of tenure; round-up size; capital and income; family labor or number of children, and finally, age of the producer (Aguinsaca-Caraguay, 2014; Crespo, Cáceres, Robledo, Soto, & Silvetti, 1996;Forero-Camacho et al, 2013;Garrido-Rubiano et al, 2017;Villalba, Gómez-Herrera, Concha-Merlo, & Ferreyra, 2016).…”
Section: With a Direct Precedent From Intermediate Technologies Publimentioning
confidence: 99%
See 1 more Smart Citation
“…En la bibliografía especializada que se consultó acerca del tema, y que en su mayoría fue seleccionada para la región en la cual se desarrolló este estudio, se hallaron referencias de numerosas variables estructurales, entre las que se priorizaron las más reiteradas, con la única intención de señalar una idea general sobre el tipo de variables involucradas: tamaño del predio o su forma de tenencia; tamaño del rodeo; capital e ingresos; mano de obra familiar o número de hijos, y, por último, edad del productor (AguinsacaCaraguay, 2014;Crespo, Cáceres, Robledo, Soto, & Silvetti, 1996;Forero-Camacho et al, 2013;Garrido-Rubiano et al, 2017;Villalba, Gómez-Herrera, Concha-Merlo, & Ferreyra, 2016).…”
Section: Introductionunclassified